Analysis of Needs for Design of Teaching Materials Based on Integrated Cognitive Conflict with Augmented Reality in Thermodynamics - Agustina, Dwi; Mufit, Fatni (Journal of Innovative Physics Teaching, 2023)
The goal of 21st century learning in the independent curriculum is that students are able to deepen concepts and strengthen competencies. Efforts that can be made to achieve this goal are the use of teaching materials that are able to increase students' understanding of concepts. This research was conducted to develop teaching materials based on cognitive conflict integrated with augmented reality technology, so it is necessary to carry out a needs analysis as an initial stage of developing teaching materials. This type of research is quantitative descriptive research, the data collection instruments used are journal analysis and teacher and student analysis questionnaire sheets. Research was conducted to determine the need for developing open materials in schools. The results of the analysis of student needs show that physics learning is still teacher-centered, technology-integrated teaching materials, especially Augmented Reality, are not yet available, and learning models that overcome students' misconceptions are not yet used. The results of this preliminary research indicate the need to develop open physics materials that are able to increase student understanding of concepts and interest in learning. The solution to this is to develop cognitive conflict-based teaching materials that are integrated with technology by utilizing augmented reality technology.